Implementation of balanced scorecard (BSC) in a Malaysian GLC: perceptions of middle managers / Hazeline Ayoup, Normah Omar and Ibrahim Kamal Abdul Rahman - Ayoup, Hazeline; Omar, Normah; Abdul Rahman, Ibrahim Kamal (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper examines the perceptions of middle managers concerning several Balanced Scorecard (BSC) implementation issues using the case study approach. Data were collected using a questionnaire which was distributed to 280 middle managers in a selected organisation. The results of the study showed that middle managers perceived a moderate level of leadership and commitment from the top management towards the BSC implementation initiatives in the company. They also perceived that the BSC had some positive implications on their performance but they did not have a clear understanding of the workings. Middle managers also perceived that the company had good data processing and information technology to support the implementation process. However, clear guidelines on their individual performance evaluation process were not provided. These results indicate that the organisations derive benefits from the implementation of the BSC. Areas that can be improved to gain more benefits from implementing the system are highlighted.